2021
DOI: 10.4314/ajcem.v22i2.17
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contamination of Naira notes circulating in Bauchi metropolis: prevalence, microbial load and detection of extended spectrum beta-lactamase producing Gram-negative bacteria

Abstract: Background: Globally, contamination of banknotes with various microbial species is increasingly being reported. This usually results from improper handling during exchange of goods and services. In the present study, we aimed to determine the microbial load, prevalence and the presence of Extended Spectrum Beta Lactamase (ESBL) among bacteria isolated from the Nigerian Naira notes circulating in Bauchi metropolis.Methodology: A total of 400 Naira notes of various denominations were randomly collected aseptical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
3
1
Order By: Relevance
“…The finding in this study further revealed that the Naira notes of lower denominations (₦5 and ₦10) were significantly contaminated with bacterial isolates. These findings support reports from other studies that lower denominations show higher levels of contamination [18,[42][43][44][45][46][47]. Lower denominations are very often handled for different daily transactions than higher denominations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding in this study further revealed that the Naira notes of lower denominations (₦5 and ₦10) were significantly contaminated with bacterial isolates. These findings support reports from other studies that lower denominations show higher levels of contamination [18,[42][43][44][45][46][47]. Lower denominations are very often handled for different daily transactions than higher denominations.…”
Section: Discussionsupporting
confidence: 91%
“…This figure is higher than the 52.5% reported in a previous study in Nigeria [18] but comparable to those in Saudi Arabia [40] and Nepal [41]. This report was, however, lower than the 93.9% reported in Cameroon [3], 97.1% reported in Ghana [42], and 100% recently reported in Nigeria [43].…”
Section: Discussioncontrasting
confidence: 60%
“…(25) E. coli was found to be the most common contaminant of 25% of Nigeria's Niara banknotes in Bauchi metropolis, followed by S. aureus (12%). (26) In Sudan, Klebsiella pneumoniae was found to be the most common contaminant of 23% of banknotes, followed by Pseudomonas stutzeri (15%) and E. coli (12%). (20) The level of banknote contamination with bacteria in the present study was found to vary depending on the denomination.…”
Section: Discussionmentioning
confidence: 99%
“…Eight samples from each denomination were collected in different sterile sample bottles and camphor was introduced to it for six (6) hours, the other samples were left untreated, the camphor was removed carefully by means of sterile forceps and 10mL of distill water was added to each denomination of the treated and the untreated samples, they were allowed to stand for two (2) hours. The isolation of microorganisms from the two groups was done by using pour plate method as described by Sam [12], both the nutrient agar and the potato dextrose agar plates were incubated and observed for the presence of growth and the colonies on nutrient agar plates were counted and expressed as colony forming unit per meal.…”
Section: Isolation Of Microorganisms From the Currency Notesmentioning
confidence: 99%
“…This mode of pathogen transfer has been implicated in serious health hazards. Microorganisms such as Rhizopus, Aspergillus flavus, Mucor, Staphylococcus aureus and have been isolated from naira notes [6], this suggests that the currency notes could serve as fomites for some infectious agents.…”
Section: Introductionmentioning
confidence: 99%